2021
DOI: 10.3390/microorganisms9122475
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Thermophilic Microbial Communities from a Deep-Sea Hydrothermal Chimney under Electrolithoautotrophic Conditions with Nitrate

Abstract: Recent studies have shown the presence of an abiotic electrical current across the walls of deep-sea hydrothermal chimneys, allowing the growth of electroautotrophic microbial communities. To understand the role of the different phylogenetic groups and metabolisms involved, this study focused on electrotrophic enrichment with nitrate as electron acceptor. The biofilm density, community composition, production of organic compounds, and electrical consumption were monitored by FISH confocal microscopy, qPCR, met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…With the recent discovery of electrical currents within deep-sea hydrothermal vents [14], a new potential energy source has been identified. As previously mentioned, recent studies have demonstrated the ability of modern electrotrophs from hydrothermal vents to grow from an external electric current, coupled with the fixation of CO2 and the reduction of different electron acceptor, such as nitrate, sulfate, CO2, O2 and iron-oxide [28][29][30]. Based on these observations, we can assume that Life have evolved to use an electrical current in combination with a range of different electron acceptors.…”
Section: Energetic Proto-metabolismmentioning
confidence: 62%
See 3 more Smart Citations
“…With the recent discovery of electrical currents within deep-sea hydrothermal vents [14], a new potential energy source has been identified. As previously mentioned, recent studies have demonstrated the ability of modern electrotrophs from hydrothermal vents to grow from an external electric current, coupled with the fixation of CO2 and the reduction of different electron acceptor, such as nitrate, sulfate, CO2, O2 and iron-oxide [28][29][30]. Based on these observations, we can assume that Life have evolved to use an electrical current in combination with a range of different electron acceptors.…”
Section: Energetic Proto-metabolismmentioning
confidence: 62%
“…In recent studies, the ability of some microorganisms from modern hydrothermal vents to grow using only electricity as an energy source has been demonstrated, either focusing on hyperthermophiles [28][29][30], or in-situ using electrical current generated from the hydrothermal fluid [31]. This metabolism was defined as a new trophic type, as compared to photo-or chemo-trophy, named electrotrophy [32].…”
Section: Electrotrophy In Modern Hydrothermal Ventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, multiple lines of evidence suggest geothermal electricity generation in deep hydrothermal systems. Nevertheless, so far we do not have characterized isolates from these field sites but Pillot et al could at least show enrichment data for cathodic growth of inocula taken at a deep-sea hydrothermal chimney (Nakamura et al 2010 ; Pillot et al 2021 ). Nevertheless, a direct interaction of isolated extremophiic microorganisms with cathodes has some biotechnological potential as it could offer the possibility to use autotrophic organisms and an electrical current as starting points for a carbon dioxide-based biotechnology.…”
Section: Introductionmentioning
confidence: 99%